Letter from Carl D. Duncan to Patricia Whiting, October 3, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan shares his experiences while traveling and discusses the development of his relationship with Whiting.